Ads to icons how advertising succeeds in a multimedia age - Springer, Paul (IG library, 2009)
The second edition of Ads to Icons examines current and future trends in advertising. Through 50 international case studies of new and iconic advertising campaigns, author Paul Springer identifies why these campaigns were successful and analyzes their contribution to the continued development of advertising.